Do children with recurrent abdominal pain grow up to become adolescents who control their weight by fasting? Results from a UK population‐based cohort. Issue 6 (3rd May 2021) - Stein, Kate; Warne, Naomi; Heron, Jon; Zucker, Nancy; Bould, Helen
Abstract: Objective: Gastrointestinal (GI) problems are common in eating disorders, but it is unclear whether these problems predate the onset of disordered eating. Recurrent abdominal pain (RAP) is the most prevalent GI problem of childhood, and this study aimed to explore longitudinal associations between persistent RAP (at ages 7 and 9) and fasting for weight control at 16. Method: The Avon Longitudinal Study of Parents and Children (ALSPAC) is a UK population cohort of children. Childhood RAP was reported by mothers and defined as RAP 5+ (5 pain episodes in the past year) in our primary analysis, and RAP 3+ (3 pain episodes) in our sensitivity analysis. Fasting for weight control was reported by adolescents at 16. We used logistic regression models to examine associations, with adjustments for potential confounders. Results: After adjustments, we found no association between childhood RAP 5+ and adolescent fasting for weight control at 16 (OR 1.30 (95% Confidence Intervals [CI] 0.87, 1.94) p  = .197). However, we did find an association between RAP 3+ and later fasting, in the fully adjusted model (OR 1.50 [95% CI 1.16, 1.94] p  = .002), and after excluding those with pre‐existing anxiety (OR 1.52 [95% CI 1.17, 1.97] p  = .002). Discussion: Our findings suggest a possible independent contribution of RAP to later risk of fasting for weight control, and RAP should be enquired about in the assessment of eating disorders. However, frequency of childhood abdominal pain (as captured by ALSPAC) may be less important to long‐term outcomes than functional impairment.